Tropical | University of Wyoming Stratospheric Aerosol Measurements - Terry Deshler (10063870) (2022)
The globally distributed stratospheric aerosol are a constant but highly variable component of the Earth’s atmosphere. They impact climate through their albedo and ozone through heterogeneous chemistry. For these reasons they must be considered in all climate prediction models, and there are a host of measurement platforms to characterize these aerosol. Their optical properties have been measured from satellites, since the late 1970s, while surface based lidar measurements have been completed regularly at a handful of locations since the mid 1970s. The first measurements, however, were completed using in situ instruments deployed on balloons and aircraft in the 1960s. In contrast to the satellite and lidar measurements which provide extinction or backscatter, the in situ measurements provide size distributions, and thus the only direct path for deriving the microphysical parameters required by the global models such as aerosol surface area, volume, and cross section. The longest continuous record of in situ stratospheric aerosol measurements has been completed at Laramie, Wyoming, 1971-2020, comprising nearly 400 individual balloon flights. The measurements from these flights since 1989 are contained in this digital archive. In addition to the flights from Laramie there are over 100 flights from McMurdo Station, Antarctica, 45 flights from Kiruna, Sweden, and a handful of flights from 13 other locations throughout the world stretching from 45˚S to 68˚N. The measurements from Laramie from 1971 – 1988 are available on the data base of the Network for the Detection of Atmospheric Composition Change, https://www.ndaccdemo.org/. This record includes the following Tropical datasets: /Aerosol_InSitu_Meas/In_Hyderabad_17N_79E_2015/ /Aerosol_InSitu_Meas/NI_Niamey_13N_2E_2006_2008/ /Aerosol_InSitu_Meas/BR_Teresina_5S_43W_2008/ /Aerosol_InSitu_Meas/AU_Darwin_13S_132E_2005_2014/ /Aerosol_InSitu_Meas/BR_Bauru_22S_49W_1997/ /Aerosol_InSitu_Meas/AU_Longreach_23S_144E_1972_1973/, UWv1.0 only ...